Children and parents with limiting long-term illness and disability (LLTI/D) in the UK: To what extent does parental LLTI/D precede or follow parenting a child with LLTI/D. (13th September 2011) - Blackburn, C*; Spencer, N; Read, J
Abstract : Objectives: To examine the relationship between child limiting long-term illness and disability (LLTI/D) and parental LLTI/D, factors associated with this relationship and the extent to which parental disability precedes or follows parenting a disabled child using the UK Office for National Statistics (ONS) Longitudinal Study (ONS-LS). Design and methods: Children born between 1981 and 1991 UK censuses who became ONS-LS members and present at 2001 were identified. Parents were identified from the 1991 and 2001 files for non-members in the same household. To test the hypothesis that children with LLTI/D are more likely to live with a parent with LLTI/D, logistic regression models were fitted on child LLTI/D by parental LLTI/D adjusted for potential confounders. To study the temporal relationship of child and parental disability, dummy variables were created for combinations of child/parent LLTI/D in 1991 and these were entered into separate logistic regression models fitted on parent or child LLTI/D in 2001. Results: Children aged 10–20 years with LLTI/D in 2001 had a significantly increased risk of having a parent with LLTI/D compared with those with no reported LLTI/D after adjustment for social disadvantage and other confounding variables (Odds Ratio (OR) 2.35(95% CI 2.10 to 2.63)). Parents without LLTI/D but with a child aged 0–10 years with LLTI/D in 1991, were more likely than those with a child without LLTI/D to develop LLTI/D by 2001 (OR 2.24 (95% CI 1.96 to 2.56). Children without LLTI/D in 1991 but with a parent with LLTI/D were more likely than those with a parent without LLTI/D to develop LLTI/D by 2001 (OR 1.66 (95% CI 1.29 to 2.13)). Conclusion: Our findings suggest that children with LLTI/D are at increased risk of living with a parent with LLTI/D. Having a child with LLTI/D appears to be associated with an increased risk of a parent developing LLTI/D in the subsequent 10 years. An increased risk of developing LLTI/D is also evident for a child whose parent has LLTI/D. The limitations of data available in the ONS-LS do not allow us to comment on the contribution of biological or social factors to these observed associations but they raise important questions for future research and implications for the social and economic well-being of families with disabled children.